Evaluation of Superficial and Internal Clogging of Geotextiles - da Silva, Jorge Luis Vieira; Lodi, Paulo César [UNESP] (Springer Nature, 2020)
The present work evaluated the clogging of nonwoven (two made of polyester, PET, and one made of polypropylene, PP) and woven (PP) geotextiles submitted to leachate flow from a municipal landfill. Long-term permeability tests were carried out by measuring the hydraulic conductivity over time. Then, scanning electron microscopy (SEM) was performed to evaluate the closure of the geotextile pores and bacterial growth. The main results obtained show a reduction in the hydraulic conductivity of the geotextiles after 35 days. The SEM results of the nonwoven geotextiles showed that the pores inside the geotextiles remained open, while a large part of the solid material was deposited on the surface of the geotextiles. Thus, the results support the idea that the process known as blinding, not clogging, occurred. In addition, SEM allowed us to visualize and confirm pore closure, showing how the formation of microbial colonies occurs and that these occur in a greater proportion in woven geotextiles since its flat surface helps the process, which was observed on a smaller scale in the other geotextiles. In this sense, SEM was essential in verifying the clogging process of geotextiles.
Keywords: Clogging; Geotextile; Hydraulic conductivity testing; Landfills; Leachate; Scanning electron microscopy